Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Sure! Let's determine the correct formula to find the distance from point [tex]\( D \)[/tex] to point [tex]\( A \)[/tex].
1. Understand the coordinates of the points:
- Point [tex]\( D \)[/tex] is at [tex]\( (0, b) \)[/tex].
- Point [tex]\( A \)[/tex] is at [tex]\( (0, 0) \)[/tex].
2. Apply the distance formula:
The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
3. Substitute the coordinates of points [tex]\( D \)[/tex] and [tex]\( A \)[/tex] into the formula:
- [tex]\( x_1 = 0 \)[/tex], [tex]\( y_1 = 0 \)[/tex]
- [tex]\( x_2 = 0 \)[/tex], [tex]\( y_2 = b \)[/tex]
Plugging these values into the distance formula, we get:
[tex]\[ \text{Distance} = \sqrt{(0 - 0)^2 + (b - 0)^2} \][/tex]
Simplify the expression:
[tex]\[ \text{Distance} = \sqrt{0 + b^2} = \sqrt{b^2} = b \][/tex]
So, Martin can use the formula to determine the distance from point [tex]\( D \)[/tex] to point [tex]\( A \)[/tex]:
[tex]\[ \sqrt{(0-0)^2 + (b-0)^2} = \sqrt{b^2} = b \][/tex]
Examining the provided options:
- Option A: [tex]\((a-a)^2+(b-a)^2=b^2\)[/tex] is incorrect.
- Option B: [tex]\((0-0)^2+(b-0)^2=b^2\)[/tex] is correct numerically but does not include the square root.
- Option C: [tex]\(\sqrt{(a-a)^2+(b-0)^2}=\sqrt{b^2}=b\)[/tex] is incorrect in the x-component.
- Option D: [tex]\(\sqrt{(0-0)^2+(b-0)^2}=\sqrt{b^2}=b\)[/tex] is the correct option.
Therefore, the correct answer is:
[tex]\[ \boxed{\text{D}} \][/tex]
1. Understand the coordinates of the points:
- Point [tex]\( D \)[/tex] is at [tex]\( (0, b) \)[/tex].
- Point [tex]\( A \)[/tex] is at [tex]\( (0, 0) \)[/tex].
2. Apply the distance formula:
The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
3. Substitute the coordinates of points [tex]\( D \)[/tex] and [tex]\( A \)[/tex] into the formula:
- [tex]\( x_1 = 0 \)[/tex], [tex]\( y_1 = 0 \)[/tex]
- [tex]\( x_2 = 0 \)[/tex], [tex]\( y_2 = b \)[/tex]
Plugging these values into the distance formula, we get:
[tex]\[ \text{Distance} = \sqrt{(0 - 0)^2 + (b - 0)^2} \][/tex]
Simplify the expression:
[tex]\[ \text{Distance} = \sqrt{0 + b^2} = \sqrt{b^2} = b \][/tex]
So, Martin can use the formula to determine the distance from point [tex]\( D \)[/tex] to point [tex]\( A \)[/tex]:
[tex]\[ \sqrt{(0-0)^2 + (b-0)^2} = \sqrt{b^2} = b \][/tex]
Examining the provided options:
- Option A: [tex]\((a-a)^2+(b-a)^2=b^2\)[/tex] is incorrect.
- Option B: [tex]\((0-0)^2+(b-0)^2=b^2\)[/tex] is correct numerically but does not include the square root.
- Option C: [tex]\(\sqrt{(a-a)^2+(b-0)^2}=\sqrt{b^2}=b\)[/tex] is incorrect in the x-component.
- Option D: [tex]\(\sqrt{(0-0)^2+(b-0)^2}=\sqrt{b^2}=b\)[/tex] is the correct option.
Therefore, the correct answer is:
[tex]\[ \boxed{\text{D}} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.